Spin effects in MoS2 and WS2 single layers. Issue 1 (14th December 2015) - Kioseoglou, G.; Korkusinski, M.; Scrace, T.; Hanbicki, A. T.; Currie, M.; Jonker, B. T.; Petrou, A.; Hawrylak, P.
Abstract : Replacing the two sublattices of carbon atoms in graphene with transition metal atoms and chalcogenide dimers results in single layers of transition metal dichalcogenides (TMDCs). TMDCs are promising new materials for light and energy harvesting, transistors, sensors and quantum information processing. One way to access the distinctive functionality of these materials is via their optical selection rules. In particular, light with positive or negative helicity is absorbed differently, therefore, understanding the interaction of circularly polarized light with various TMDCs should enable future applications. Using the examples of MoS2 and WS2 we summarize some recent results that illustrate the potential of these materials. First, when optically excited with circularly polarized light, single layers of MoS2 can emit light with an appreciable polarization. Depolarization mechanisms can be subsequently explored by monitoring the polarization of emitted photoluminescence as a function of the excess energy supplied to the system. As the energy of the pumping light increases further from the emission channel, the emission quickly becomes depolarized. The dominant relaxation mechanism is identified as phonon‐assisted intervalley scattering. In single layers of WS2 containing electron gas, the main emission channel is from negatively charged excitons, or trions. In the presence of a two‐dimensional electron gas this trion emission is circularly polarized at zero magnetic field, even when excited with linearly polarized light. This spontaneous circular polarization of the trion has a linear dependence on magnetic field and can be attributed to the existence of a valley polarized state of the two‐dimensional electron gas. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : The authors review their recent experimental and theoretical research on optical properties of single‐layer transition metal dichalcogenides WS2 and MoS2 . For MoS2, the authors discuss the origins of circular polarization of light detected in emission as well as dominant depolarization mechanisms. For WS2, the emission of charged excitons excited with linearly polarized light reveals circular polarization at zero magnetic field. It is proposed that this spontaneous polarization is due to the formation of a valley‐polarized state in the low‐density electron gas, and can be further manipulated by the external magnetic field.